Optimalisasi Waktu Pengapian untuk Mesin Bensin: Studi Performa dan Emisi - Ramadhan Nur, Hamid; Muhammad, Rouf; Sugiyarto; Dwi Ardika, Rizki; Rizki Bintoro, Sefrian; Safi'i, Muhamad; Isdhianto, Irfan (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2025)
Multiple factors affect the performance of spark ignition (SI) engines, with ignition time being a crucial element. Accurate ignition timing is essential for optimizing engine performance and regulating exhaust emissions. This study examines the performance, fuel efficiency, and exhaust emissions of a 125cc engine by evaluating ignition timing variations at 550, 600, and 650 CA BTDC. The study involved direct evaluation of engine performance with a dynamometer test for torque and power, assessment of fuel consumption using a measuring cup, and investigation of exhaust emissions using a gas analyzer. The precise calibration of ignition timing discrepancies was accomplished via a motorbike diagnostic tool. The findings demonstrate that a 600 CA BTDC ignition timing variation produces excellent engine performance and efficient exhaust emissions. Optimal ignition timing profoundly influences engine performance and emission quality, rendering it essential for enhancing efficiency and mitigating environmental effects. Consequently, the results of this study may serve as a reference for practical applications in the field. Keywords: ignition timing, engine performance, emission, fuel consumption.